Brain-inspired computing : Second International Workshop, BrainComp 2015, Cetraro, Italy, July 6-10, 2015, revised selected papers /: Second International Workshop, BrainComp 2015, Cetraro, Italy, July 6-10, 2015, revised selected papers. (2016) - Unknown
No abstract available